Experimental Study on Interaction between Ce-Nd Alloy and Stainless Steel - RUAN Zhangshun, ZHANG Ruiying, WANG Yuhui, TU Menghe, FU Xiaogang, LONG Bin (Yuanzineng kexue jishu)
In integrated fast reactor, metal fuel is used for its advantages in fuel reprocessing and recycling. However, under high temperature and irradiation, complex mechanical and chemical interactions between the fuel and cladding significantly limit fuel lifespan and burnup depth. The mechanical interactions are basically solved by responding designs: metal fuels swell at low burnup levels, exerting pressure on the cladding and causing deformation, which is addressed by designs include an initial gap filled with sodium to accommodate expansion and improve heat transfer. A fission gas plenum helps maintain low internal pressure, enabling higher burnup. Key chemical interaction includes the following categories. 1) Intergranular corrosion: Fission products like Ce and Nd migrate to the cladding, weakening it through corrosion. 2) Eutectic melting: U and Pu diffuse into the cladding while Fe and Ni migrate into the fuel, forming low-melting-point alloys near the interface. Eutectic points can be as low as 650 ℃ for U-Pu-Fe systems. Lanthanides like Ce and Nd show similar phenomena. 3) Decarburization: Carbon migrates from cladding to fuel, altering the cladding’s structure. However, this effect is less significant. To mitigate these issues, 10% Zr was added to the fuel to raise its melting point. Protective coatings on cladding, such as Cr or Cr nitrided layers, were also used to suppress fuel-cladding chemical interactions (FCCI). Coating methods could be utilized for interior coating of claddings, including electroplating and metal-organic chemical vapor deposition (MOCVD). In this study, interactions between Ce-Nd alloys and cladding materials (304 stainless steel, 12Cr ferritic/martensitic steel, and electroplated Cr-coated 304 SS) in sodium (Na) and argon (Ar) environments were tested at 550 ℃ and 650 ℃ for about 50 hours. SEM and EDS analyses were used to assess diffusion behavior. At 550 ℃, Cr-coated samples reduce FCCI diffusion depth by 50% compared to uncoated 304 SS. However, coating cracks allow limited Ce-Nd infiltration. At 650 ℃, severe diffusion occurs, and coating defects nullify Cr’s protective effect, resulting in similar diffusion depths for coated and uncoated samples. Liquid sodium may accelerate diffusion in non-contact areas, but variability at 650 ℃ makes this effect inconclusive. In summary, Cr coatings show promise in reducing FCCI at lower temperatures, but their effectiveness at high temperatures is limited by defects.